A review of the world wide work on the breeding and production of Groupers - Al Mukhtar, Mustafa A. (Iraqi Journal of Aquaculture, 2022)
The Groupers fishes consist many important marketable species, in the world and the Gulf region, but it's populations were gravely reduced. The production of Groupers was either by fisheries- based aquaculture, or by artificial breeding. The baby Groupers were caught during early summer from the costal waters, estuaries and tidal pools. The Groupers are mostly Protogynous hermaphrodites, and the hormones implantation were used for sex reverse. The enrichment of the brooders diet must be done with polyunsaturated fatty acids, that to amelioration the eggs quality and increasing larval quality and survival rate. The hormone injection was used either for artificial insemination or semi-natural breeding. The induced brooders were placed in spawning tanks, and then the floating fertilized eggs were collected by collecting funnel. The hatching troughs were used for hatching the fertilized eggs. The larvae could be produced in raceways, earthen ponds, and outside cement tanks. The live food must produce in the hatchery for the feeding of the newly hatching larvae. Then the fingerlings could be reared to marketing size for a period of 6-8 months.